Effects of β‐carotene on oxazolone‐induced atopic dermatitis in hairless mice. Issue 9 (8th August 2019) - Kake, Takamichi; Imai, Masahiko; Takahashi, Noriko
Abstract: Skin acts as a barrier, which protects internal tissues and promotes moisture retention. Atopic dermatitis (AD) is an inflammatory skin disease associated with a variety of genetic and environmental factors that involve helper T cells. β‐Carotene (provitamin A) exhibits antioxidant activity and activates the immune system. However, it is not clear whether inflammation in AD skin is improved by posttreatment with β‐carotene. In the current study, we investigated the effects of β‐carotene on the skin of hairless mice with oxazolone‐induced inflammation/oedema (Ox‐AD mice). We found that skin inflammation was significantly reduced by oral administration of β‐carotene. In addition, treatment with β‐carotene suppressed protein levels of TNF‐α, IL‐1β and MCP‐1, as well as mRNA expression associated with IL‐1β, IL‐6, IL‐4 and Par‐2 in skin tissues. Furthermore, the mRNA and protein levels of filaggrin, a structural protein in the epidermal stratum corneum, were elevated by β‐carotene administration as compared with Ox‐AD mice. β‐Carotene significantly reduced the activity of proMMP‐9, but not proMMP‐2. These results suggest that in Ox‐AD mice, β‐carotene improves skin inflammation by suppressing the expression of inflammatory factors, promoting filaggrin expression and reducing MMP‐9 activity. β‐Carotene is a potent anti‐inflammatory agent that improves the barrier functions of AD skin.